How to Engage Resistant Students in Classes of Innovation and Entrepreneurship? - Celeste B. Holmbye; Allan B. Bjeld (Proceedings of the ENTRENOVA - ENTerprise REsearch InNOVAtion Conference, Rovinj, Croatia, 12-14 September 2019, 2019)
The paper presents a case study of an example in educational design of teaching innovation and entrepreneurship at a higher education (Academy Profession Programme). A challenge when teaching innovation is, that students resist engaging themselves to it, as it represents change (Dibrov, 2015) and is different from other ways of attending classes of education. We experience the same, students at the Administration, logistics and marketing management do not see themselves as innovators or entrepreneurs and resist engaging in the classes. When they do participate, they still do not take on the roles. However, during fall 2018 we experienced some groups of students changing their minds about innovation and entrepreneurship. They went from resistance to enjoying being innovators and entrepreneurs. The goal of the paper is to understand what it takes to create room for students to take on the role as innovator/entrepreneur so we can design classes that invites for this. The purpose of the research is to find out if there is anything we can take into consideration, when we plan and implement our elective courses, which results in more engaged and motivated students.
Keywords: I21; 330; innovation; entrepreneurship; engaged students; motivation; participation; creativity management